2010
DOI: 10.1364/oe.18.008790
|View full text |Cite
|
Sign up to set email alerts
|

Subwavelength metal-optic semiconductor nanopatch lasers

Abstract: We report on near infrared semiconductor nanopatch lasers with subwavelength-scale physical dimensions (0.019 cubic wavelengths) and effective mode volumes (0.0017 cubic wavelengths). We observe lasing in the two most fundamental optical modes which resemble oscillating electrical and magnetic dipoles. The ultra-small laser volume is achieved with the presence of nanoscale metal patches which suppress electromagnetic radiation into free-space and convert a leaky cavity into a highly-confined subwavelength opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
180
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(182 citation statements)
references
References 32 publications
1
180
1
Order By: Relevance
“…However, PICs require optoelectronic devices with electrical control, and electrical contacts greatly perturb these cavity modes, making electrically driven lasing a difficult task. By embedding our nanoresonator structure inside a metaloptic cavity [28][29][30] , we show that nanoresonator produces electrically driven stimulated emission. Although stimulated emission is observed under both continuous wave (CW) and pulsed pumping, full laser oscillation has not yet been achieved.…”
Section: Resultsmentioning
confidence: 99%
“…However, PICs require optoelectronic devices with electrical control, and electrical contacts greatly perturb these cavity modes, making electrically driven lasing a difficult task. By embedding our nanoresonator structure inside a metaloptic cavity [28][29][30] , we show that nanoresonator produces electrically driven stimulated emission. Although stimulated emission is observed under both continuous wave (CW) and pulsed pumping, full laser oscillation has not yet been achieved.…”
Section: Resultsmentioning
confidence: 99%
“…A popular structure comprises of a metal encapsulated high gain material 17,63 . However, several other forms have been demonstrated, such as nanopatch devices 64 , with a size of just 500 nm in their largest dimension, or vertical travelling-wave core-shell structures terminated by Bragg gratings 65 . The non-plasmon mode metallic lasers often have Q factors as low as 100 -200, but can have Qs of several thousand 63 depending on the structure and nature of the mode.…”
Section: Small Laser Types and Their Characteristicsmentioning
confidence: 99%
“…Like small dielectric lasers, the more recently developed small metallic and plasmonic lasers can be realized with a widely varying range of laser resonator structures, from plasmonic photonic crystal structures and open dielectric-loaded waveguides 20,[69][70][71]74,81,92,93 to small encapsulated devices or metallic nano-particle resonators [17][18][19][63][64][65] . There is potential for further development of different forms of metallic waveguides, permitting possibly better tradeoffs between small volume and metal induced losses.…”
Section: Future Trends and Challengesmentioning
confidence: 99%
“…Spasers and plasmonic nanolasers with deep subwavelength cavities represent one of the important frontiers of research in nanophotonics and nanotechnology in general. [1][2][3][4][5][6][7][8][9][10] While metals have been used as parts of the laser cavity for long wavelengths, 11 it remains an open question if metals such as silver or gold can be used to make a subwavelength cavity in the near infrared or shorter wavelength, due to dramatically increased metal loss in these wavelengths, especially at RT. 12 Theoretical studies 10,13 that accounted for wavelength compression and metal loss near surface plasmon polariton (SPP) resonance showed that it was indeed possible to realize a net positive gain in a semiconductor-metal core-shell structure.…”
mentioning
confidence: 99%
“…3 While great progress has been made in the past few years in nanolasers with deep subwavelengthsized metal cavities [1][2][3][4][5][6][7][8] and spacers, 2,9 the realization of RT continuous wave (cw) operation under electrical injection has remained elusive. Despite intensive activities worldwide, subwavelength-cavity RT lasing has been demonstrated only under optical [5][6][7] or electrical-pulse pumping, 4 or under cw electrical pumping but at low temperature. 4 RT cw lasing under electrical injection has been observed only for a metallic cavity that is larger than the wavelengths.…”
mentioning
confidence: 99%